2020
DOI: 10.1007/s10663-020-09476-4
|View full text |Cite
|
Sign up to set email alerts
|

Total factor productivity, its components and drivers

Abstract: We consider how the growth of total factor productivity (TFP) was affected by R&D, trade, information and communication technology, and catching-up for the period from 1990 to 2006. Our contributions are: Firstly, to decompose TFP growth into two distinct measures for catching-up and for innovation using the Malmquist index; secondly, to update related investigations. Summarizing our findings, catching-up effects are statistically important, whereas frontier shifts tend to be smaller with increasing distance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…This stability suggests that technical efficiency has made a significant contribution towards the capabilities of sustainable development of coal mining cities, which could be the hallmark for other mining cities to adopt, with respect to resource allocation and utilization. In line with endogenous growth theories, R&D is a source of (TFPCH) TFP growth [32]. The decomposition effect gives an indication of the role of technological efficiency as R&D influences EFFECH, which leads to a robust upward movement of the technological frontier (TECHCH) with a growth of about 43.7%.…”
Section: Conversional Decomposition Of Sustainable Development Capabilities Of Coal Mining Citiesmentioning
confidence: 73%
See 2 more Smart Citations
“…This stability suggests that technical efficiency has made a significant contribution towards the capabilities of sustainable development of coal mining cities, which could be the hallmark for other mining cities to adopt, with respect to resource allocation and utilization. In line with endogenous growth theories, R&D is a source of (TFPCH) TFP growth [32]. The decomposition effect gives an indication of the role of technological efficiency as R&D influences EFFECH, which leads to a robust upward movement of the technological frontier (TECHCH) with a growth of about 43.7%.…”
Section: Conversional Decomposition Of Sustainable Development Capabilities Of Coal Mining Citiesmentioning
confidence: 73%
“…The various challenges of the coal mining industries for now and the future are strongly linked to better approaches towards sustainability and transformation with the proposed way forward being all-round change caused by innovation through R&D and an industrial structure upgrade. R&D is a major source of novelty and technological advancement, while enhancement in technological capabilities positively affect production [32], and efficiency, creating a link between R&D and output. Cameron, et al [33] found a direct influence of R&D on total factor productivity (TFP) and this builds the nexus between R&D and TFP.…”
Section: Coal Mining Sector Challenges and Innovation In Randdmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of policy might be, however, difficult in the less developed regions as they face significant structural obstacles in diminishing the productivity gap (see eg. Haider et al, 2020, Bednář & Halásková, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the period 1990 to 2006, Haider et al (2021) looked at how R&D, trade, and ICT affected TFP growth in 25 European countries, Japan, and the United States. They broke down TFP growth into two components: catching up and innovation (frontier shifts).…”
Section: Introductionmentioning
confidence: 99%